Pragmatist Philosophy and Dance : Interdisciplinary Dance Research in the American South - Eric Mullis (Palgrave Macmillan, 2019)
This book investigates how Pragmatist philosophy as a philosophical method contributes to the understanding and practice of interdisciplinary dance research. It uses the author's own practice-based research project, Later Rain, to illustrate this. Later Rain is a post-dramatic dance theater work that engages primarily with issues in the philosophy of religion and socio-political philosophy. It focuses on ecstatic states that arise in Appalachian charismatic Pentecostal church services, states characterized by dancing, paroxysms, shouting, and speaking in tongues (glossolalia). Research for this work is interdisciplinary as it draws on studio practice, ethnographic field work, cultural history, Pentecostal history and theology, folk aesthetics, anthropological understandings of ecstatic religious rituals, and dance history regarding acclaimed works that have sought to present aspects of religious ecstasy on stage; Doris Humphrey's The Shakers (1931), Mark Godden’s Angels in the Architecture (2012), Martha Clarke’s Angel Reapers (2015) and Ralph Lemon’s Geography trilogy (2005). The project thereby demonstrates a process model of dance philosophy, showing how philosophy and dance artistry intertwine in a specific creative process. This book investigates how Pragmatist philosophy as a philosophical method contributes to the understanding and practice of interdisciplinary dance research. It uses the author's own practice-based research project, Later Rain, to illustrate this. Later Rain is a post-dramatic dance theater work that engages primarily with issues in the philosophy of religion and socio-political philosophy. It focuses on ecstatic states that arise in Appalachian charismatic Pentecostal church services, states characterized by dancing, paroxysms, shouting, and speaking in tongues (glossolalia). Research for this work is interdisciplinary as it draws on studio practice, ethnographic field work, cultural history, Pentecostal history and theology, folk aesthetics, anthropological understandings of ecstatic religious rituals, and dance history regarding acclaimed works that have sought to present aspects of religious ecstasy on stage; Doris Humphrey's The Shakers (1931), Mark Godden’s Angels in the Architecture (2012), Martha Clarke’s Angel Reapers (2015) and Ralph Lemon’s Geography trilogy (2005). The project thereby demonstrates a process model of dance philosophy, showing how philosophy and dance artistry intertwine in a specific creative process.
Keywords: Performing arts; Dance; Pragmatism; Theater